DESIGN OF SOLAR THERMAL COLLECTOR TOOL WITH THERMOSIFON SYSTEM - Rahman, Mulia; Lanya, Budianto; ., Tamrin (The University of Lampung, 2013)
Limited availability of fossil energy requires us to find for alternative energy to meet our needs. Solar thermal collector with thermosifon system is one of environmentally friendly alternative energy. The thermosifon system is a natural pump which work based on density difference between cool water and hot water, so that no electric pump is needed. The purpose of this research was to create a mean of collecting solar thermal energy with thermosifon system. The research steps consist of designing, manufacturing, and testing. Thermal collector was made with dimension of 1,5 m long, 1,0 m wide and 1,0 m high, with storage tank capacity of 20 lt.Â Collector testing was conducted by putting the equipment at an open space from a clock 08:00 â 16:00. It was found that the highest efficiency of solar collector (11,2 %) occurred on July 11, 2012 with an average solar intensity of 756 W/m2, where as the lowest efficiency Â (8,8 %) occurred on July 7, 2012, with the average solar intensity 479 W/m2. The highest average temperature of the storage tank was 44,7 ÂºC on July 13, 2012 while the lowest average temperature was 35,3 ÂºC on July 12, 2012. Keywords: Solar Collector, Thermosifon, Radiaton Intensity, Thermal Efficiency